WHEAT FLOUR HUMIDITY VARIATION WITH UV-VIS RADIATION DOSE REVEALED BY SPECTRAL AND CHEMOMETRIC STUDIES - IULIANA MIHAELA LAZĂR; ALINA MIHAELA MOROI; IRINA LOREDANA IFRIM; NICOLETA VARTOLOMEI; ALISA-VASILICA ARUŞ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2012)
The cells’ exposure to UV radiation induces mutations of the cellular components by its action on DNA, protein synthesis and enzymatic activities. Different varieties of wheat flour were treated with UV-B, UV-A, Vis radiation and compared with untreated samples. The IR spectra for these components were recorded with a Bruker FTIR spectrophotometer using an ATR method, at 4 cm-1 resolution. The paper proposes a comparative study of unmaturing flour behavior under UV-Vis and natural radiations in order to observe the physico-chemical changing by FTIR spectroscopy. At small doses of irradiation (up to 2 h) the humidity of the samples decreases and then it significantly increases, most pronounced in Gruia’s case where the humidity is reaching 74.4% of the initial value. Middle infrared spectral studies reveal an inverse weak linear correlation between Amide I region (1650 cm-1) (R-squared value: -0.3168) and an inverse medium linear correlation assigned to area alcohol O-H band at 3290 cm-1 (R-squared value: -0.6064) with the irradiation dose variables. Strong direct linear correlations confirmed by R-squared value: 0.7835 are found between alcohol O-H band at 3290 cm-1 and humidity percentage parameter.